Non-Oak Ridge RFLP patterns in the Neurospora crassa multicent-2 strains - S. D. Haedo; M. R. Mautino; A. L. Rosa (Fungal Genetics Reports, 1992)
The N. crassa strain multicent-2 (FGSC 4488) is widely used for RFLP mapping (Metzenberg et al. 1984 Neurospora Newsl. 31:35-39). The genetic background of multicent- 2 is considered as being largely "Oak Ridge". However, by studying RFLP patterns, we have recently found that a region in the multicent-2 linkage group VII differs considerably from that of the standard wild type "Oak Ridge" 74-OR23-1A (FGSC 987) (Haedo et al. 1992 Genetics, in press). We extend here this observation to a 40 kb region on the left arm of linkage group I. Table I shows that the analyzed region on chromosome I is largely "Oak Ridge" both in multicent-2 and, as expected, the Mauriceville-1c genome.